Constraints on mantle viscosity and Laurentide ice sheet evolution from pluvial paleolake shorelines in the western United States: Datasets - Austermann, Jacky; Chen, Christine Y.; Lau, Harriet C.P.; Maloof, Adam C.; Latychev, Konstantin (Zenodo, 2019)
*********** Please view the README.txt file for detailed documentation of data. *********** Title: Constraints on mantle viscosity and Laurentide ice sheet evolution from pluvial paleolake shorelines in the western United States: Datasets Version: 1.0 Date of Release: 2019/12/16 Identifier: 10.5281/zenodo.3576251 Associated publication: Austermann, J., Chen, C.Y., Lau, H.C.P., Maloof, A.C., and Latychev, K. (2019) Constraints on mantle viscosity and Laurentide ice sheet evolution from pluvial paleolake shorelines in the western United States. Earth and Planetary Science Letters . doi: 10.1016/j.epsl.2019.116006 Link to publication: https://doi.org/10.1016/j.epsl.2019.116006 Suggested citation: Please reference the associated publication above when using any datasets or materials described in the README file. Contact information: Jacky Austermann (jackya@ldeo.columbia.edu) and Christine Y. Chen (cychen.earth@gmail.com) -------------------------------------------------------------------------------------------------------------------------------------------------------------------------------- This directory contains the following datasets: SHORELINE FEATURE ELEVATION DATA Bonneville_Provo_Sehoo_shoreline_feature_elev_Austermann2019_EPSL.xlsx : shoreline feature elevation measurements of the Bonneville, Provo, and Sehoo lake stages of Lake Bonneville and Lake Lahontan; original measurements were made by Adams et al. (1999), Chen and Maloof (2017), and Currey (1982) MODELED RECONSTRUCTIONS OF LAKE VOLUME AND PALEOTOPOGRAPHY LakeBonneville_NAICE_l20.ump02p25.lmp5VM5.mat: model output for Lake Bonneville, including reconstructions of lake volume and paleotopography LakeLahontan_NAICE_l20.ump02p25.lmp5VM5.mat : model output for Lake Lahontan, including reconstructions of lake volume and paleotopography : {"references": ["Adams, K.D., Wesnousky, S.G., Bills, B.G., 1999. Isostatic rebound, active faulting, and potential geomorphic effects in the Lake Lahontan basin, Nevada and California. Geol. Soc. Am. Bull. 111, 1739\u20131756.", "Chen, C.Y., Maloof, A.C., 2017. Revisiting the deformed high shoreline of Lake Bon-neville. Quat. Sci. Rev.159, 169\u2013189.", "Currey, D.R., 1982. Lake Bonneville: Selected Features of Relevance to Neotectonic Analysis. Open-File Report 82-1070. U.S. Geological Survey, 31 pages."]}